224OPatient-centred outcomes with maintenance olaparib in newly diagnosed patients with advanced ovarian cancer (OC) and a BRCA mutation in the phase III SOLO1 trial to support the clinical benefit of prolongation of progression-free survival (PFS). (24th November 2019) - Friedlander, M L; Moore, K N; Colombo, N; Scambia, G; Kim, B-G; Oaknin, A; Lisyanskaya, A; Floquet, A; Leary, A; Sonke, G S; Gourley, C; Banerjee, S; et al.
Abstract: Background: In SOLO1 (NCT01844986; GOG-3004), maintenance olaparib significantly improved PFS vs placebo (HR 0.30; 95% CI 0.23–0.41; Moore et al. NEJM 2018) in patients with newly diagnosed advanced OC, a BRCA mutation and clinical complete or partial response after platinum-based chemotherapy. Most patients in the maintenance setting are well following first-line treatment; thus, it is important to show that extending PFS is not at the expense of decreased health-related quality of life because of toxicity. We assessed the duration of 'good quality of life' while on maintenance therapy based on time without significant symptoms of toxicity (TWiST) and quality-adjusted PFS (QAPFS) which both incorporate the adverse effects experienced by patients on maintenance therapy. Methods: Patients were randomized 2:1 to olaparib tablets 300 mg bid or placebo. Patient-centred outcomes were assessed by QAPFS (product of adjusted mean estimate of the EuroQol 5D-5L single-index utility score from randomization to disease progression and mean PFS time) and TWiST (period without significant symptoms post-randomization and before disease progression or censoring for progression) in a post hoc analysis in the full analysis set. Results: Of 391 randomized patients, 260 received olaparib and 130 placebo (1 patient did not receive placebo). Mean QAPFS and TWiST improved to a clinically meaningful extent with olaparib vs placebo, with highly significant between-group improvements of at least 12 months (Table). Conclusions: There were clinically meaningful patient-centred benefits with maintenance olaparib in both QAPFS and TWiST supporting the substantial benefit of PFS improvement seen with olaparib in newly diagnosed advanced OC. Clinical trial identification: NCT01844986. Editorial acknowledgement: Medical writing assistance was provided by Gillian Keating, MBChB, from Mudskipper Business Ltd, funded by AstraZeneca and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (MSD). Legal entity responsible for the study: AstraZeneca and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (MSD). Funding: AstraZeneca and Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: M.L. Friedlander: Honoraria (self), Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: MSD; Advisory / Consultancy: Lilly; Advisory / Consultancy: Takeda; Advisory / Consultancy, Uncompensated: AbbVie. K.N. Moore: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Advaxis; Advisory / Consultancy: Clovis; Advisory / Consultancy: Tesaro; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Immunogen; Advisory / Consultancy: VBL Therapeutics; Advisory / Consultancy: Merck; Advisory / Consultancy: Janssen; Advisory / Consultancy: Aravive; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Eisai; Advisory / Consultancy: Samumed; Advisory / Consultancy: Oncomed. N. Colombo: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Tesaro; Honoraria (self), Advisory / Consultancy: PharmaMar; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Immunogen; Advisory / Consultancy: Biocad; Advisory / Consultancy: Seattle Genetics. A. Oaknin: Advisory / Consultancy: Roche; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: PharmaMar; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: Tesaro; Advisory / Consultancy: Immunogen; Advisory / Consultancy: Genmab. A. Floquet: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy, Congress support: Roche; Advisory / Consultancy, Congress support: PharmaMar; Advisory / Consultancy, Congress support: Tesaro. A. Leary: Honoraria (self), Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: Biocad; Advisory / Consultancy: Tesaro; Advisory / Consultancy: MSD; Advisory / Consultancy: GamaMabs; Advisory / Consultancy: Seattle Genetics. G.S. Sonke: Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Merck; Research grant / Funding (self): Novartis; Research grant / Funding (self): Roche. C. Gourley: Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Tesaro; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Nucana; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Clovis Oncology; Honoraria (self), Advisory / Consultancy: Foundation One; Honoraria (self), Advisory / Consultancy: MSD; Honoraria (self), Advisory / Consultancy: Sierra Oncology; Honoraria (self), Advisory / Consultancy: Cor2Ed; Research grant / Funding (self): Novartis; Research grant / Funding (self): Aprea. S. Banerjee: Honoraria (self), Research grant / Funding (self): AstraZeneca; Honoraria (self): Tesaro; Honoraria (self): Clovis Oncology; Honoraria (self): Merck; Honoraria (self): PharmaMar; Honoraria (self): Roche; Honoraria (self): Seattle Genetics; Honoraria (self): Nucana. A. Oza: Non-remunerated activity/ies, Steering Committee: AstraZeneca; Non-remunerated activity/ies, Steering Committee: Clovis Oncology; Non-remunerated activity/ies, Steering Committee: Tesaro. A. González-Martín: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Tesaro; Advisory / Consultancy: PharmaMar; Advisory / Consultancy: Roche; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: Immunogen; Advisory / Consultancy: Genmab; Advisory / Consultancy: Pfizer; Advisory / Consultancy: MSD. C. Aghajanian: Honoraria (self): Tesaro; Honoraria (self): ImmunoGen; Honoraria (self): Clovis Oncology. E. Lowe: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. R. Hettle: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. E. Flood: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. P. Disilvestro: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Tesaro. All other authors have declared no conflicts of interest.